Análises morfo-fisiológicas em plantas de Allamanda blanchetii sob déficit hídrico - Alves, Magnólia Martins (2016)
Drought can be seen as a natural phenomenon, very common in the Northeast, is commonly attributed to the deviation from the normal amount of rainfall. The study of physiological and anatomical parameters of species of Caatinga, developed in different water conditions, may help to clarify the mechanisms used by the species facing low water availability in the soil. Allamanda blanchetii is an endemic species of the Caatinga and belongs to the family Apocynaceae, popularly known as allamanda-rosa. This study was conducted in a greenhouse Laboratório de Ecologia Vegetal, do Centro de Ciências Agrárias, Universidade Federal da Paraíba, campus II, Areia, PB. The objective of the research was to evaluate the growth, gas exchange, relative water content and stomatal density A. blanchetii under water stress conditions. The experimental design was completely randomized with six water treatment (100%, 80%, 60%, 40% and 20% of the pot capacity and irrigation suspension) with eight replications. Weekly reviews were plant height, number of leaves. At the end of the experiment at 112 days, determined the leaf area, specific leaf area, leaf area ratio, matter of the leaves (MSF), stems (MSC) and roots (MSR), biomass allocation of these components [sheets (ABF), stems (ABC) and roots (ABR)], root length (cm) and root system volume (VSR), leaf area (AF), specific leaf area (AFE) and leaf area ratio (RAF). In addition, three measurements were made of the variables related to gas exchange with 66, 85 and 105 days after sowing [photosynthesis (A), transpiration (E), stomatal conductance (Gs), internal carbon (Ci), the difference between temperature leaf and air], stomatal density, SPAD and relative water content (TRA). The results suggest that plants grow best in water levels of 100% and 80% of the pot capacity, without presenting significant morphological and physiological changes. Fluid restriction impairs the gas exchange and growth in treatments of 60% and 40% of the pot capacity, and the treatment plans 20% could not stand the stress applied. The AF and RAF were significantly affected, but no changes to the AFE. The root system had a significant reduction in volume despite the deepening of the main root less sensitive to water stress. The SPAD and relative water content of leaves were not influenced by the water system to which the plants were submitted. It can be concluded that reducing the growth of the leaf surface, gas exchange and changes in stomatal density are the main effects of water stress on young plants of A. blanchetti.